2009
DOI: 10.1007/s00011-008-8141-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine induction by a linear 1,3-glucan, curdlan-oligo, in mouse leukocytes in vitro

Abstract: Taken together, these results suggest that CRDO stimulated mouse leukocytes to induce the production of cytokines, and the mechanism of the effect of CRDO on leukocytes is different from that of SCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…ZYM was a less potent cytokine inducer than curdlan, which was also the case in our experiments. Hida et al suggested that the difference in affinity for dectin-1 influenced the ability of these β-glucans to induce the production of cytokines [29]. They demonstrated that the branched glucan oligosaccharides were recognized by dectin-1 with higher affinity than the comparable linear glucan, which resulted in a greater production of cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…ZYM was a less potent cytokine inducer than curdlan, which was also the case in our experiments. Hida et al suggested that the difference in affinity for dectin-1 influenced the ability of these β-glucans to induce the production of cytokines [29]. They demonstrated that the branched glucan oligosaccharides were recognized by dectin-1 with higher affinity than the comparable linear glucan, which resulted in a greater production of cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…In bone marrow-derived dendritic cells, bglucan induced productions of TNF-a and IL-6. Taken together, these results suggested that b-glucan stimulated mouse leukocytes to induce the productions of cytokines (Hida et al, 2009). LPS-stimulated NO production in RAW 264.7 cells was reported to be an effective approach for evaluating the anti-inflammatory activity of b-glucan.…”
Section: Introductionmentioning
confidence: 90%
“…β-Glucan is a water-soluble fibre found in cereals, as well as in yeast, bacteria, algae and mushrooms (145) . The EPS β-glucan has been reported to have many health promoting properties, including immunomodulatory effects (146)(147)(148)(149) , lowering serum cholesterol levels (145,150) , antiosteoporotic (151) , antitumourigenic, anticytotoxic and antimutagenic effects (152,153) . Furthermore, oat β-glucan has also been associated with the ability to modulate satiety, thus controlling appetite (154,155) .…”
Section: Microbial Production Of Exopolysaccharidesmentioning
confidence: 99%